ForDigitStress: presentation and evaluation of a new laboratory stressor using a digital job interview-scenario - Becker, Linda; Heimerl, Alexander; André, Elisabeth (Frontiers in Psychology, 2023)
Since the Covid-19 pandemic, working environments and private lives have changed dramatically. Digital technologies and media have become more and more important and have found their way into nearly all private and work environments. Communication situations have been largely relocated to virtual spaces. One of these scenarios are digital job interviews. Job interviews are usually – also in the non-digital world – perceived as stressful and associated with biological stress responses. We here present and evaluate a newly developed laboratory stressor which is based on a digital job interview-scenario. N = 45 healthy people participated in the study (64.4% female; mean age: 23.2 ± 3.6 years; mean body mass-index = 22.8 ± 4.0 kg/m2). Salivary alpha-amylase (sAA) and cortisol were assessed as measures for biological stress responses. Furthermore, perceived stress was rated at the time points of the saliva samplings. The job interviews lasted between 20 – 25 minutes. All materials including instructions for the experimenter (i.e., the job interviewer) as well as the data set used for statistical analysis are publicly available as well as a multimodal data set. Typical subjective and biological stress response-patterns were found, with peak sAA and perceived stress levels immediately after the job interviews and peak cortisol concentrations 5 minutes afterwards. Women experienced the scenario as more stressful than men. Cortisol peaks were higher for participants who experienced the situation as a threat in comparison to participants who experienced it as a challenge. Associations between the strength of the stress response with further person characteristics and psychological variables such BMI, age, coping style, and personality were not found. Overall, our method is well-suited to induce biological as well as perceived stress, mostly independent of person characteristics and psychological variables. The setting is naturalistic and easily implementable in standardized laboratory settings.